2015
DOI: 10.1038/ismej.2015.163
|View full text |Cite
|
Sign up to set email alerts
|

Non-pathogenic Rhizobium radiobacter F4 deploys plant beneficial activity independent of its host Piriformospora indica

Abstract: The Alphaproteobacterium Rhizobium radiobacter F4 (RrF4) was originally characterized as an endofungal bacterium in the beneficial endophytic Sebacinalean fungus Piriformospora indica. Although attempts to cure P. indica from RrF4 repeatedly failed, the bacterium can easily be grown in pure culture. Here, we report on RrF4's genome and the beneficial impact the free-living bacterium has on plants. In contrast to other endofungal bacteria, the genome size of RrF4 is not reduced. Instead, it shows a high degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 64 publications
5
108
0
Order By: Relevance
“…However, a knockout line for this protein was not 211 Sharma et al (2008), Glaeser et al (2016) and demonstrated that P. indica 212 forms an intimate association with Rhizobium radiobacter F4, an alpha-Proteobacterium. The 213 endophytic bacterium shows a high degree of similarity to the plant pathogenic R. radiobacter…”
mentioning
confidence: 99%
“…However, a knockout line for this protein was not 211 Sharma et al (2008), Glaeser et al (2016) and demonstrated that P. indica 212 forms an intimate association with Rhizobium radiobacter F4, an alpha-Proteobacterium. The 213 endophytic bacterium shows a high degree of similarity to the plant pathogenic R. radiobacter…”
mentioning
confidence: 99%
“…Bacteria lacking the capability to colonize and infection can enter plant endophytic niches via wounds and cracks on the plant, which is documented as the passive mode of endophytic colonization (Christina et al, 2013) (Fig.1). work conducted by Compant et al (2005; and Glaeser et al (2016).…”
Section: Distribution Of Endophytic Bacteria and Colonization Patternsmentioning
confidence: 95%
“…Current evidence also reveals that some bacteria live in symbiosis with plant endophytic fungi (Desirò et al, 2015;Glaeser et al, 2016). Interestingly, some endofungal bacteria colonize plants in a similar fashion as their fungal host.…”
Section: Distribution Of Endophytic Bacteria and Colonization Patternsmentioning
confidence: 99%
See 2 more Smart Citations